E-Retailing study: A bibliometric analysis and systematic literature review - William Widjaja; Yudhi Widya Arthana Rustam (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
Along with the increasing popularity of online shopping in Indonesia, the E-retailing business has increased in recent years in Indonesia. This research aims to analyze the trends and developments of e-retailing in Indonesia and globally. This research is a type of literature study research with a qualitative approach. The analysis technique used is bibliometric analysis and systematic literature review using VOS viewer software. The results showed eight main clusters related to e-retailing: chatbot, customer satisfaction, purchase intention, customer experience, artificial intelligence, social media, and mobile commerce. This shows that chatbots, customer satisfaction, purchase intention, and customer experience are important factors that influence the success of e-retailing. This research also shows that e-retailing is still new and needs to be continuously developed. This can be seen from the low density of research related to this topic.